Influence of Socioeconomic Factors on Mental Health Service Utilization among Urban Dwellers in India - Patel, Aarar (American Journal of Health, Medicine and Nursing Practice, 2024)
Purpose: The aim of the study was to assess the influence of socioeconomic factors on mental health service utilization among urban dwellers in India. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Socioeconomic status (SES) was identified as a crucial determinant, with individuals from lower SES backgrounds being less likely to utilize mental health services compared to those from higher SES backgrounds. This disparity was attributed to various factors such as financial constraints, lack of access to appropriate healthcare facilities, and stigma associated with seeking mental health support. Implications to Theory, Practice and Policy: Social determinants of health theory, health belief model and ecological systems theory may be used to anchor future studies on assessing the influence of socioeconomic factors on mental health service utilization among urban dwellers in India. Develop tailored interventions targeting specific socioeconomic barriers to mental health service utilization, such as affordability, transportation, and stigma reduction programs. Advocate for policy reforms that prioritize equitable access to mental healthcare services for all urban residents, regardless of socioeconomic status.